Pengaruh Kontrol Diri Terhadap Perilaku Membolos Peserta Didik - Fajar Putri Ambarwati; Tritjahjo Danny Soesilo; Setyorini Setyorini (Universitas Muhammadiyah Enrekang, 2020)
The purpose of this study was to examine the effect of self-control on truancy behavior of students. Self-control which is an individual's ability to read the situation himself and his environment. Students in a school have different characteristics. One of them is about truancy behavior. The results showed that there was an influence between self-control and school stress on bullying behavior, so that students. There was a decrease in truancy behavior at school after being given group counseling.